Analysis of Legal Efforts Against the Supporting Rights of a Prisoner's Wife in a Detention Center (Case Study of Medan Class 1 Detention Center) - Indi Sintia; Khalid (Warmadewa Press, 2024)
Marriage is a gateway for the creation of rights and responsibilities between men and women who are united by the family. However, certain situations arise when some married people cannot fully fulfill their duties and obligations as a couple, and the husband cannot fully fulfill his wife's needs, such as a husband who, with the status of a prisoner, cannot fulfill his wife's rights in the form of spiritual and physical support. With this, the author wants to examine how and what kind of efforts can be made to fulfill the living rights of a wife whose husband is imprisoned. In this research the author conducted empirical legal research. Empirical law is legal research carried out by conducting studies on the topics to be discussed by conducting interviews and field observations carried out by the author. And the result of this research is that not all efforts to fulfill the living rights of a prisoner's wife can be fulfilled and facilitated by the Medan Class I Detention Center. Birth support at the Medan Detention Center has carried out guidance activities where from the results of this work inmates can get premiums or wages which can be given by prisoners to their wives as fulfillment of birth support. And regarding spiritual support, the Medan Class I Detention Center cannot facilitate all of these subsistence needs. What can be facilitated in relation to this subsistence is a room for family visits and a telephone shop if the inmate misses and wants to confide in his wife.